Using financial statement data as economic indicators for urban governance: the case of Antwerp - Ann Verhetsel; Frank Witlox; Kaatje Molenberghs (Belgeo)
In this paper, the focus is on the interaction between high-quality urban policy-making on the one hand and the issue of data needs to construct useful indicators on the other hand. Such an approach implies that first an evaluation is to be made of the trends and developments that influence the urban development process structurally in order to distinguish some of the important keystones for a justified urban policy. Having a notion of what the urban cornerstones are and how they relate to one another, attention is then paid to the data that are required to monitor the dynamics of these cornerstones. Given that our focus is mainly on monitoring the urban economic dimension, the use of company-related data at district level (i.e. financial statement data obtained by the National Bank of Belgium) seems an interesting starting point. The data are first described and analysed statistically. Next, the methodological framework to construct a number of economic urban indicators is explained and tested. The city of Antwerp is taken as case study.